IMF Research Bulletin, Summer 2017. (IMF Research Bulletin; IMF Research Bulletin ;, 2017)
The Summer 2017 issue of the IMF Research Bulletin highlights new research such as recent IMF Working Papers and Staff Discussion Notes. The Research Summaries are 'Structural Reform Packages, Sequencing, and the Informal Economy (by Zsuzsa Munkacsi and Magnus Saxegaard) and 'A Broken Social Contract, Not High Inequality Led to the Arab Spring' (by Shantayanan Devarajan and Elena Ianchovichina). The Q and A section features 'Seven Questions on Fintech' (by Tommaso Mancini-Griffoli). The Bulletin also includes information on recommended titles from IMF Publications and the latest articles from the IMF Economic Review.